Manajemen Konflik Kolaborasi Sebagai Upaya Meningkatkan Kualitas Pendidikan di Madrasah dan Sekolah - Syarifah Nur; Elviana Elviana; Halim Ersya Putra (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2026)
Conflict is an inevitable phenomenon in educational environments due to differences in characteristics, interests, perceptions, and goals among school members. If not managed properly, conflict can disrupt the learning process, weaken social relationships, and negatively affect educational quality. This study aims to analyze the role of collaborative conflict management in improving the quality of education in madrasahs and schools. The research employed a qualitative approach using a library research method by reviewing various books, scientific journals, and relevant literature related to conflict management and education. The findings indicate that collaborative conflict management, implemented through effective communication, deliberation, discussion, negotiation, and cooperation, can facilitate constructive and sustainable conflict resolution. Furthermore, the application of collaborative conflict management contributes to strengthening cooperation among school members, creating a harmonious and conducive learning environment, and improving teacher performance as well as student learning outcomes. School principals play a strategic role as mediators and facilitators in guiding conflict resolution processes fairly and participatively. Therefore, collaborative conflict management can serve as an effective strategy for enhancing educational quality and fostering a positive educational climate in madrasahs and schools.